History and Developments of Schools Administration in Nigeria: From Natives to Present - Victor Olugbenga Ayoko; Florence Aragba; Francis Sohe; Kelechukwu Joel Chimeremeze (International Journal of Education and Teaching Zone)
This paper discussed the trends in school administration and educational development from the time of the natives until now. Secondary data was used to support the points raised in the paper using an interpretive research paradigm by sourcing data from print and online resources. Several reformations and national educational policies were implemented at intervals to channel the developmental course. The finding from this study showed that incessant strike actions by the university unions, the proscription of the earlier approved private universities and cause, and the merging of some institutions during the military era were a setback to the expected development. Access to higher education is improved with the licensures of private universities and the embrace of open distance education. Challenges include corruption, decayed infrastructures, cultism, examination malpractices, poor ranking, underbudgeting for education, poor research output, brain drain, politicization of education, school dropout, and so on. It is recommended that the government increase the educational budgetary allocation, and the appropriate government agencies should monitor educational activities.